2011
DOI: 10.1074/jbc.m110.197434
|View full text |Cite
|
Sign up to set email alerts
|

Primary Sequence That Determines the Functional Overlap between Mitochondrial Heat Shock Protein 70 Ssc1 and Ssc3 of Saccharomyces cerevisiae

Abstract: The evolutionary diversity of the HSP70 gene family at the genetic level has generated complex structural variations leading to altered functional specificity and mode of regulation in different cellular compartments. By utilizing Saccharomyces cerevisiae as a model system for better understanding the global functional cooperativity between Hsp70 paralogs, we have dissected the differences in functional properties at the biochemical level between mitochondrial heat shock protein 70 (mtHsp70) Ssc1 and an unchar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
22
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 57 publications
1
22
0
Order By: Relevance
“…However, the disruption of SSC3 in the conditional ssc1-3 strain resulted in heightened cold sensitivity when grown on glycerol compared to the ssc1-3 strain alone, suggesting a role for Ssc3 in protection against cold stress when Ssc1 is partially defective (16). Contrary to the above-described evidence, recent data showed that SSC3, when overexpressed in the ssc1⌬ strain complemented with the SSC1 gene on a URA3-marked plasmid, cannot support growth after counterselection for the loss of the complementing plasmid on 5-fluoroorotic acid (5-FOA) (330). These results suggest that SSC3 may not be competent to replace all the biological functions of SSC1 when the latter is absent, as opposed to being compromised by a point mutation.…”
Section: Mitochondrial Hsp70smentioning
confidence: 51%
See 1 more Smart Citation
“…However, the disruption of SSC3 in the conditional ssc1-3 strain resulted in heightened cold sensitivity when grown on glycerol compared to the ssc1-3 strain alone, suggesting a role for Ssc3 in protection against cold stress when Ssc1 is partially defective (16). Contrary to the above-described evidence, recent data showed that SSC3, when overexpressed in the ssc1⌬ strain complemented with the SSC1 gene on a URA3-marked plasmid, cannot support growth after counterselection for the loss of the complementing plasmid on 5-fluoroorotic acid (5-FOA) (330). These results suggest that SSC3 may not be competent to replace all the biological functions of SSC1 when the latter is absent, as opposed to being compromised by a point mutation.…”
Section: Mitochondrial Hsp70smentioning
confidence: 51%
“…In support of this conjecture, fluorescence anisotropy measurements showed that Ssc3 exhibited a lower affinity with a generic Hsp70-binding peptide than Ssc1. Using chimeras of Ssc1 and Ssc3, the D-helix within the SBD of both proteins was shown to be responsible for their differential affinities for client proteins (330). These functional differences may explain the observation that Ssc3 is present in only a small subset of closely related fungi, including S. cerevisiae, Saccharomyces bayanus, and Candida glabrata.…”
Section: Mitochondrial Hsp70smentioning
confidence: 92%
“…The initial translocation across the machinery is inner membrane potential dependent, and the final step is driven by ATPase activity of the import motor (11)(12)(13). The mitochondrial Hsp70 (mtHsp70), with the aid of accessory factors such as J-proteins, plays a critical central role during the process.…”
mentioning
confidence: 99%
“…For preparation of antibody to Tim21, a fragment corresponding to amino acids 103 to 229 was cloned into the pET-3a vector and purified from the supernatant fraction using Escherichia coli. BL21(DE3) cells, as previously described (51). For preparation of antibody to Pam17, the ORF was cloned in the pET-3a vector and protein was reconstituted from the pellet fraction using the C41 expression strain according to previously published protocols (51).…”
mentioning
confidence: 99%
“…BL21(DE3) cells, as previously described (51). For preparation of antibody to Pam17, the ORF was cloned in the pET-3a vector and protein was reconstituted from the pellet fraction using the C41 expression strain according to previously published protocols (51). To raise antibodies against Tim17, a C-terminal peptide (CEAPSSQPLQA) was used for immunization.…”
mentioning
confidence: 99%